Pengaruh Campuran dan Rasio Bahan Pembentuk Komposit terhadap Karakteristik Komposit Bioplastik - Sitepu, Syah Banu Putra; Harsojuwono, Bambang Admadi; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): JuniDO - 10.24843/JRMA.2021.v09.i02.p01, 2021)
This research aims to determine the effect of the mixture and the ratio of the composites and their interactions to the characteristics of the bioplastic composites and to determine the mix and ratio of the composites that produce the best characteristics of the bioplastic composites. The experimental design of this study used a randomized block design method. Factor I is a mixture of composite materials consisting of maizena-glucomannan, maizena-chitosan, and maizena-carrageenan. The second factor is the ratio of the composite material mixture which consists of 5 levels, namely 100: 0, 75:25, 50:50, 25:75 and 0: 100. The experiment resulted in 15 treatment combinations and were grouped into 2 groups when the process of making bioplastic composites was obtained, so that 30 experimental units were obtained. Data were analyzed for their diversity and continued with Duncan's multiple comparison test. The observed variables which tensile strength, elongation at break, modulus young, swelling, and biodegradation time. The results showed that the mixture and the ratio of the composites forming a very significant effect on tensile strength, elongation at break, elasticity, and swelling. The interaction has a very significant effect on tensile strength, elasticity and swelling and significantly affects the elongation at break of bioplastic composites. Meanwhile, the mixture and the ratio of the ingredients to form the composites had no significant effect on the biodegradation time. Maizena:glucomannan composite with ratio (25:75) produced the best characteristics of bioplastic composites with tensile strength values of 6.99 MPa, elongation at break of 16.5%, elasticity 42.39 MPa, swelling 78.78% and biodegradable time of 7 days. There are 2 variables that have met the standard, namely: elongation at break of bioplastic composites that meet the plastic Standard SNI 7188.7: 2016 and biodegradation time has met the international plastic standard ASTM 5336 and 3 variables that do not meet the standards, namely: Tensile strength (6,99 MPa) and elasticity (42,39 MPa) do not meet the Plastic Standard SNI 7188.7: 2016 and swelling (39,1%) does not meet international plastic standards (EN 317). Keywords : bioplastic composites, maizena, glucomannan, chitosan, carrageenan